Cytokines Level (Il8 and Il17) in Pregnant Women with Toxoplasmosis in Khartoum State - Wahaj M. M; Satti, A. B; Abdalla H.S; Ahmed S. Kabbashi (Journal of Parasite Research, 2019)
Toxoplasmosis is one of the most important zoonotic diseases worldwide caused by Toxoplasma gondii that leads to abortion or hydrocephalus during pregnancy. It’s a comparative cross-sectional one designed to assess immunoglobulins and cytokines in pregnant women. A total of 300 venous blood samples were collected from each pregnant woman and centrifuged to obtain serum. Patient’s information was recorded in a questionnaire previously designed for the purpose of analysis. In addition, 40 uninfected women were enrolled in the study as control group to assess the level of IL8 and IL17 cytokines. The overall seropositive rate of Toxoplasma gondii infection was 22.6%. Within the positive cases of study population, only 16 and 13 showed positive results of IL8, IL17 respectively. The results showed highly significant increase in the mean serum level of IL8 (210.25pg/ml) and IL17 (203.15 pg/ml) when compared to the control group who showed 68.9 pg/ml and 54.8 pg/ml respectively. The serum level of proinflammatory cytokines investigated in this study seems to be increased in patients with serological evidence of Toxoplasma gondii infection. Our study concludes that IL-17 and IL-8 involved in the induction of inflammation and toxoplasmosis disease.
Keywords: toxoplasmosis